Scoping Low-Cost Measures to Nowcast Sub-Hourly Solar Radiations for Buildings. (September 2019) - Chen, L; Du, H; Li, Y
Abstract: Solar energy, as a clear, renewable and promising resource, has brought tremendous value for carbon emission reduction in the last three decades. However, the uncertainty of solar radiation brings significant challenges to the renewable heat and electrical system for buildings. Thus, many different solar radiation forecasting methods, such as Numerical Weather Prediction Methods (NWP), Statistical Methods, Top-Down Methods, Bottom-Up Methods and Hybrid Methods have been developed to make the best guess on future solar radiations. Based on the meteorology definition, nowcasting refers to the forecast of the temporal horizon from the next few seconds up to six hours. Predicting solar radiation within this range are extremely challenging, but crucial for solar energy system operation. This paper firstly reviewed the state of art of solar radiation forecasting methods and compared the key features of each method. According to the advantage and costs of each method, this paper then proposed a methodology to generate high accuracy low-cost solar radiation nowcast data for optimising building solar thermal system performance and related control strategies. Note that this paper focused on the scoping study of methodology rather than field experiments, and further research with experiments data will be reported in a journal publication.